BERPIKIR KREATIF SISWA KELAS X SEKOLAH MENENGAH ATAS MUJAHIDIN PONTIANAK TAHUN 2018 - Liliana Liliana; Mohammad Asrori; Yuline Yuline (Universitas Tanjungpura, 2019)
Abstract Creative learning in students on their own has been owned by each student itself, only their order in terms of experience and thinking of the utilization of this creativity does not run as optimally. Therefore, researchers want to know more about the creative thinking of tenth grade students of Pontianak High School Mujahidin. The problem in this study was